Islamic Education and Civilized Democracy: Haedar Nashir’s Polite Communication Strategy from a Qur’anic and Pragmatic Perspective - Santoso, Dwi (Nadwa: Jurnal Pendidikan Islam, 2024)
Polite political communication is the main foundation in creating a civilized democracy. Haedar Nashir, as an Islamic thinker and General Chair of PP Muhammadiyah, emphasized the importance of ethics and morality in political communication. This article discusses Haedar Nashir's polite communication strategies from the perspective of the Al-Quran and pragmatic communication theory, especially in speech act analysis. By using Geoffrey Leech's principles of politeness and the concept of communication in Islam, this article identifies how Haedar Nashir builds a narrative that is inclusive, moderate, and oriented towards social harmony. Furthermore, the role of Islamic education is highlighted as a medium for cultivating ethical values, adab, and wasathiyah, which are essential in shaping leaders capable of practicing polite communication in the political sphere. Based on an analysis of Haedar Nashir's five speech acts, it was found that polite political communication is able to strengthen social stability, increase public trust, and prevent polarization. This article emphasizes that a healthy democracy requires communication that is based on politeness, wisdom and Islamic values